Relationship of F-Be mineralization to granites and syenites at the Ermakovka deposit (Western Transbaikalia) - G.S. Ripp; I.A. Izbrodin; M.O. Rampilov; A.A. Tomilenko; E.A., Lastochkin; V.F. Posokhov (Geologica Acta, 2020)
The paper presents the mineralogical and geochemical characteristics of two groups of hydrothermal rocks and their relation with subalkaline granites of the Ermakovskoe deposit. The first group includes fluorite-phenakite-bertrandite ore bodies, occurring outside the granite massif. The second group is presented by silicification bodies with sulfates, phosphates, kaolinite, muscovite and hematite. It bears REE (rare earth elements) mineralization (monazite, florencite, xenotime) and occurs within the massif. Our research included isotopic analyses of Sr, Nd and O, studies of trace, including rare-earth element compositions and age determination (U-Pb) of apatite from F-Be ores. Geochemical and isotopic studies are not according with relation between F-Be ores and granites. This is proven by the absence of Be-mineralization in granites and schlieren pegmatites, and a sharp difference in composition of their fluid phases. A reductive fluid specification forming F-Be ores (containing CH4, H2, N2, CO2 and H2S), contrasts sharply with fluid specification of granites. The granites are characterized by high oxygen fugacity, due to ferrous iron, sulfates and phosphates. Besides isotopic composition of oxygen in quartz (7.4 and 5.1‰ δ18О V-SMOW respectively), initial Sr ratios (0.7056-0.7065 and 0.707-0.709 respectively) and REE compositions are different.